Recent Publications (Quarterly Journal of Economics, 1950)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 64, Issue 4, November 1950, Pages 653–655, https://doi.org/10.1093/qje/64.4.653 Published: 01 November 1950